Semantic association search and rank method based on spreading activation for the Semantic Web - Myungjin Lee; Wooju Kim (2009 IEEE International Conference on Industrial Engineering and Engineering Management, 2009)
As the information on the Web dramatically increases, the existing web reveals more and more limitations in information search because Web pages are designed only for human consumption by mixing content with presentation. In order to improve this situation, the semantic Web based on ontology comes on the stage by W3C, and it will bring a significant advancement in Web search. To do this, the semantic Web must provide different search methods based on relationships between resources. In this paper, we propose a semantic association search methodology that consists of how to find relevant information for a given user's query in the ontology, that is, a semantic network of resources and properties. From this work, users can search the semantically associated resources with their query as valuable and important information.